Leveraging Social Media to Enhance Historical Awareness: A Case Study of the Inspect History YouTube Channel - Jumardi, Jumardi; Andi, Andi; Naredi, Hari; Fadillah, Siti Roudotul (AL-ISHLAH: Jurnal Pendidikan, 2024)
Limitations in educational curricula, ineffective teaching methods, and insufficient resources can hinder a nation's ability to foster historical awareness. However, advancements in information and communication technology (ICT) present opportunities to address these challenges. The rise of social media platforms, especially YouTube, has become a powerful tool in disseminating historical knowledge. This study employs a qualitative research design with a case study approach, focusing on the YouTube channel "Inspect History." Data were collected through observations of the channel's content, online interviews, and document analysis. The study specifically examines how this platform contributes to enhancing historical consciousness. The "Inspect History" YouTube channel, with 580 thousand subscribers and 257 videos as of July 20, 2022, demonstrates the effectiveness of animated videos in fostering historical awareness. Viewers reported increased engagement with and understanding of historical events through the platform's accessible content. The findings suggest that social media, particularly YouTube, can significantly enhance the public's understanding of history. The case of "Inspect History" illustrates how well-curated digital content can compensate for limitations in traditional educational settings, providing an engaging alternative for learning. This study highlights the potential of social media platforms to promote historical awareness. The success of "Inspect History" underscores the value of utilizing digital tools to overcome educational barriers and cultivate a deeper public understanding of history in the digital era.